Revitalisasi Wisata Mata Air Sendang Sebagai Upaya Pengembangan Ekowisata dan Ikon Berbasis Budaya Lokal, Ngimbrang - Lusi Musfiroh; Muhammad Zidan ’Ilma; Abiyyu Zakly; Arum Rizqi Aprilia; Hanik Laily Rizka Maharani; Eriska Nanda Damayanti; Nudha Andira Adam; Ibnu Sabannuloh; Arfiana Fitri Damayanti; Aristiya Wilda Ningrum; Slamet Widodo Setiawan; Eka Nafiyanto; Zulfa Nafisatun Nisa; Dwian Hartomi Akta Padma Eldo (Pelayanan Unggulan : Jurnal Pengabdian Masyarakat Terapan, 2025)
Revitalization of Sendang spring tourism has an important role in developing local culture-based ecotourism. This community service program aims to implement the Sendang spring tourism revitalization strategy to support the development of local culture-based ecotourism and identify revitalization strategies that are in accordance with ecotourism principles and maintain the cultural values ​​of the surrounding community. This service is carried out through various activities that include environmental conservation, strengthening the local economy, and preserving the culture of the surrounding community. The method used in this program is a participatory approach with community involvement in observation, training, and direct assistance. The results of the activities show that revitalization through a culture-based ecotourism approach can increase public awareness of environmental conservation, strengthen the local economy, and maintain cultural values. The main challenge in this program is building a balance between resource utilization and sustainable conservation efforts. The conclusion of this service confirms that the revitalization of Sendang spring contributes to increasing the attractiveness of ecological and cultural-based tourism, and provides benefits to the community in a sustainable manner.